Advances on Applications of Bioactive Natural Compounds - Seca, Ana M. L; Gallardo, Eugenia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Natural compounds, from terrestrial and marine sources, are the result of an evolutionary process which originated in compounds with great structural diversity, multiple biological activities and miscellaneous applications. A large and very active research field is dedicated to identifying biosynthesized compounds; to improve/develop new methodologies to produce/reuse natural compounds; to assess their potential; and to understand their mechanism of action. This Special Issue brings together excellent original and review works, focused on the most recent advances related to the secondary metabolites' composition of natural sources, and the proposal of new applications for their constituents, such as therapeutic agents, and pesticides or food ingredients.